Islamic Education Textbook Studies: Teachers' Duties and Responsibilities as EducatorsIslamic Education Textbook Studies: Teachers' Duties and Responsibilities as Educators - Nadia, Ami Putri (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study departs from the Islamic philosophical premise that tarbiyah, ta’līm, and ta’dīb constitute a divine mandate that shapes the identity, duties, and moral accountability of teachers. Although the literature on Islamic education frequently discusses teacher professionalism, existing studies tend to emphasize pedagogical and competency standards grounded in Western learning theories while overlooking the ethical-spiritual obligations historically articulated in classical Islamic manuscripts. This research addresses that gap by analyzing how teachers’ duties and obligations are conceptualized in selected Islamic educational texts and mapping them against contemporary teacher competency frameworks. Using qualitative manuscript study and thematic content analysis, two analytical distinctions emerge: duties (professional functions such as lesson design, instruction, assessment, guidance, and parent partnership) and obligations (ethical responsibilities rooted in sincerity, amānah, adab, spiritual exemplarity, and accountability before God). The findings demonstrate that teacher professionalism in Islamic education becomes holistic only when pedagogical competence is grounded in moral–spiritual obligations, not merely technical performance. The study contributes to the renewal of Islamic teacher professionalism by offering an integrated framework—bridging classical concepts of mu’allim, murabbī, and mu’addib with contemporary competency standards—to strengthen ethical integrity and the relevance of Islamic education in a plural, digital era.